2016
DOI: 10.1136/sextrans-2016-052786
|View full text |Cite
|
Sign up to set email alerts
|

What explains anorectal chlamydia infection in women? Implications of a mathematical model for test and treatment strategies

Abstract: ObjectivesFemale anorectal Chlamydia trachomatis (chlamydia) infections are common irrespective of recent anal sex. We explored the role of anorectal infections in chlamydia transmission and estimated the impact of interventions aimed at improved detection and treatment of anorectal infections.MethodsWe developed a pair compartmental model of heterosexuals aged 15–29 years attending STI clinics, in which women can be susceptible to or infected with chlamydia urogenitally and/or anorectally and men urogenitally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 25 publications
2
42
0
Order By: Relevance
“…Nevertheless, a previous modelling study exploring the impact of testing interventions and partner notification in a general population showed that including concurrency hardly affected the results [49]. Third, similar to other chlamydia modelling studies [36,38], we did not include a period of immunity after natural clearance of chlamydia in our model, because it is not clear if and for how long a period of immunity exists [50]. Fourth, we performed univariate uncertainty analyses only, changing a single parameter and keeping the other parameters fixed at their baseline values.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Nevertheless, a previous modelling study exploring the impact of testing interventions and partner notification in a general population showed that including concurrency hardly affected the results [49]. Third, similar to other chlamydia modelling studies [36,38], we did not include a period of immunity after natural clearance of chlamydia in our model, because it is not clear if and for how long a period of immunity exists [50]. Fourth, we performed univariate uncertainty analyses only, changing a single parameter and keeping the other parameters fixed at their baseline values.…”
Section: Discussionsupporting
confidence: 69%
“…First, the participants were divided into two sexual behaviour groups (SB groups) based on the reported number of partners: low-and high-risk sexual behaviour groups, similar to previous research [36,37]. Individuals with three or more partners were considered the high-risk group, because the majority of heterosexual STI clinic visitors in the Netherlands report three or more partners per year [20,38], and STI clinic visitors tend to be at higher risk for STIs than the general population [25]. Second, individuals were divided into two risk perception groups based on the personal risk estimates for chlamydia (RP groups): low and high risk perception.…”
Section: Definition Of Sexual Behaviour and Risk Perception Groupsmentioning
confidence: 99%
“…In contrast to genital CT infections, the clinical relevance (ie, capacity to cause infection and morbidity) and public health implication (ie, transmission potential) associated with rectal CT infections in women are debated 9 10. One of the key questions is whether rectal CT detection by nucleic acid amplification tests (NAATs) represents a true (ie, viable) rectal infection.…”
Section: Introductionmentioning
confidence: 99%
“…cervix) is transferred to, and establishes infection, in another anatomic site (e.g. rectum) [41]; contamination from another anatomical site such as for example may occur during toileting causing contamination on an anal swab as it is inserted into the anal canal for sampling, and [42]; oral ingestion causing a reservoir of infection in the rectum [43]. However, establishing which of these is responsible is extremely challenging and would require longitudinal data with frequent specimen collection and the use of an anoscope to collect swabs from higher up the rectal canal where anorectal CT infection is likely to establish.…”
Section: Discussionmentioning
confidence: 99%